Pengembangan Pariwisata Kabupaten Magetan Dalam Perspektif Pembangunan Berkelanjutan - Sri Ambarini; Muhammad Mudjib Musta’in; Khoiruddin (Journal of Public Power, 2020)
Tourism objects in Magetan Regency, are tourism objects that continue to develop and need to be developed to achieve the expected perspective, namely supporting welfare and improving the community's economy. The purpose of this study is to find out, describe and analyze tourism development in the perspective of sustainable development, the impact on the condition of the economic, social/cultural, and environmental aspects of the community as well as supporting and hindering factors in tourism development in Magetan Regency. With this type of qualitative descriptive research, data sources or sources are obtained from events, informants, and documentation. The technique of collecting is interview, observation and documentation. Data analysis is done by processing and preparing data for analysis, reading the entire data. coding data, describing data and interpreting or interpreting data. The validity of the data is carried out by means of certainty of research participation, and trisngulation. The result is that the development of tourism in Magetan Regency with a Sustainable Development Perspective is carried out through mutual cooperation through the role of stakeholders. The impact of tourism development in Magetan Regency on the economy is very influential on the welfare of the surrounding community and APBD. There are positive and negative impacts of tourism on the social/cultural and environment of the surrounding community. The supporting factors for tourism are the advantage of geographical location, the entry fee for tourism is still cheap, Improving the welfare of the surrounding community. And the obstacle to tourism development is the lack of availability of tourism supporting facilities and infrastructure, the lack of investor interest in tourism development in Magetan, Human Resources (HR) still low, There are still many street vendors selling on the roadside, less parking space.